2010
DOI: 10.1111/j.1742-1241.2010.02424.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk evaluation and antiretroviral therapy effects in an HIV cohort: implications for clinical management: the CREATE 1 study

Abstract: Aims:The aim of this study is to determine the cardiovascular disease (CVD) risk profile of a large UK HIV cohort and how highly active antiretroviral therapy (HAART) affects this.Methods:It is a cross-sectional study within a large inner city hospital and neighbouring district hospital. A total of 1021 HIV positive outpatients representative of the complete cohort and 990 who had no previous CVD were included in CVD risk analysis. We recorded demographics, HAART history and CVD risk factors. CVD and coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 33 publications
2
44
1
2
Order By: Relevance
“…There were 37,110 HIV-infected patients in total, with females representing approximately 28%. Thirty-one studies (61%) were conducted in low-and middleincome countries with the highest number of studies (n = 8) reported in India [22,27,29,30,45,47,59,61], followed by six studies in Nigeria [24,31,34,36,50,54], and four studies each in Brazil [23,32,41,44], Norway [15,16,55,62], and USA [17,39,40,53]. Nonetheless, studies conducted in high-income countries were generally larger in size (n = 30,120 participants), compared with studies conducted in low-and middleincome countries (n = 7488).…”
Section: Resultsmentioning
confidence: 97%
“…There were 37,110 HIV-infected patients in total, with females representing approximately 28%. Thirty-one studies (61%) were conducted in low-and middleincome countries with the highest number of studies (n = 8) reported in India [22,27,29,30,45,47,59,61], followed by six studies in Nigeria [24,31,34,36,50,54], and four studies each in Brazil [23,32,41,44], Norway [15,16,55,62], and USA [17,39,40,53]. Nonetheless, studies conducted in high-income countries were generally larger in size (n = 30,120 participants), compared with studies conducted in low-and middleincome countries (n = 7488).…”
Section: Resultsmentioning
confidence: 97%
“…The study by Aboud et al [6] was not a study of cardiovascular disease (CVD) or coronary heart disease (CHD) events. It was a study of predicted CVD or CHD using a Framingham risk formula.…”
mentioning
confidence: 99%
“…This study should not have been included in the meta-analysis. A second problem, but minor by comparison, is that the two estimates cited from Aboud et al [6] are correlated and cannot simply be pooled.…”
mentioning
confidence: 99%
“…Levando em consideração o risco cardiovascular inerente ás PVHA sob HAART 14 , essa tendência ao aumento do componente ectomórfico parece ser benéfica, uma vez que a literatura 17 constatou a ectomorfia como o único componente a exibir relação inversa com a pressão arterial sistólica (PAS) e pressão arterial diastólica (PAD), ou seja, à medida que a ectomorfia aumenta, a PAD e PAS diminui, sugerindo que uma maior linearidade pode melhorar o perfil de risco cardiovascular. Essa ideia é reforçada pela relação inversa entre a ectomorfia e índices gerais de adiposidade 18 , sendo este fator considerado como um dos maiores preditores de DCNT.…”
Section: Discussionunclassified